Study of Post-Peak Strain Softening Mechanical Behaviour of Rock Material Based on Hoek–Brown Criterion - Qibin Lin (Advances in Civil Engineering, 2018)
In order to build the post-peak strain softening model of rock, the evolution laws of rock parameters m,s were obtained by using the evolutionary mode of piecewise linear function regarding the maximum principle stress. Based on the nonlinear Hoek–Brown criterion, the analytical relationship of the rock strength parameters m,s, cohesion c, and friction angle φ has been developed by theoretical derivation. According to the analysis on the four different types of rock, it is found that, within the range from 0 to σ3min, the peak hardness of the rock becomes smaller as the confining pressure increases and the degree of rock fragmentation decreases as well. The post-peak stress-strain curves obtained from the developed softening model are in good agreement with the laboratory test results under different confining pressures. In conclusion, the analytical method is reasonable, and it can predict the post-peak mechanical behaviour of rock well, which provides a new thought for the rock-softening simulation.